CELF1 Mediates Connexin 43 mRNA Degradation in Dilated Cardiomyopathy. Issue 10 (27th October 2017) - Chang, Kuei-Ting; Cheng, Ching-Feng; King, Pei-Chih; Liu, Shin-Yi; Wang, Guey-Shin
Abstract : Rationale: : Downregulation of Cx43 (connexin 43), the major cardiac gap junction protein, is often associated with arrhythmia, dilated cardiomyopathy (DCM), and heart failure. However, the cause of the reduced expression remains elusive. Reinduction of a nuclear RNA-binding protein CELF1 (CUGBP Elav-like family member 1) in the adult heart has been implicated in the cardiac pathogenesis of myotonic dystrophy type 1. However, how elevated CELF1 level leads to cardiac dysfunction, such as conduction defect, DCM, and heart failure, remains unclear. Objective: : We investigated the mechanism of CELF1-mediated Cx43 mRNA degradation and determined whether elevated CELF1 expression is also a shared feature of the DCM heart. Methods and Results: : RNA immunoprecipitation revealed the involvement of CELF1-regulated genes, including Cx43, in controlling contractility and conduction. CELF1 mediated Cx43 mRNA degradation by binding the UG-rich element in the 3′ untranslated region of Cx43. Mutation of the nuclear localization signal in CELF1 abolished the ability to downregulate Cx43 mRNA, so nuclear localization was required for its function. We further identified a 3′ to 5′ exoribonuclease, RRP6 (ribosomal RNA processing protein 6), as a CELF1-interacting protein. The interaction of CELF1 and RRP6 was RNA-independent and nucleus specific. With knockdown of endogenous RRP6, CELF1 failed to downregulate Cx43 mRNA, which suggests that RRP6 was required for CELF1-mediated Cx43 mRNA degradation. In addition, increased CELF1 level accompanied upregulated RRP6, and reduced Cx43 level was detected in mouse models with DCM, including myotonic dystrophy type 1 and CELF1 overexpression models and a myocardial infarction model. Importantly, depletion of CELF1 in the infarcted heart preserved Cx43 mRNA level and ameliorated the cardiac phenotypes of the infarcted heart. Conclusions: : Our results suggest a mechanism for increased CELF1 expression downregulating Cx43 mRNA level and a pathogenic role for elevated CELF1 level in the DCM heart. Abstract : Supplemental Digital Content is available in the text.